Rural–urban differences in healthcare utilization across different outcomes in Portugal - Martinho, Júlia (2025)
Background: Urbanization influences healthcare access and utilization, contributing to health disparities. This study aims to assess the effect of degree of urbanization on healthcare utilization in Portugal, where urbanization levels are above global average. Methods: Utilizing data from the 2019 National Health Survey, this cross-sectional study analyzed the association between degree of urbanization and outcomes including general and specialist consultations, flu vaccination, colonoscopy, and wait times. Adjusted prevalence ratios (aPR) were estimated using Poisson regression models. Results: Less populated areas had increased wait times (aPR = 1.54; 95% confidence intervals [95% CI]: 1.06–2.24) and lower colonoscopy utilization (aPR = 0.86; 95% CI: 0.78–0.95). Flu vaccination rates were higher in rural (aPR = 1.15; 95% CI: 1.03–1.30) and suburban areas (aPR = 1.16; 95% CI: 1.04–1.30). No significant association was found for general/specialist consultations or excessive wait times. Conclusions: Geographic constraints limit healthcare access in less populated areas. Urban areas showed suboptimal flu vaccination rates, suggesting a need for improved immunization strategies. Addressing geographical disparities is crucial for ensuring equitable healthcare access across Portugal.